الدفع الإلكتروني في ظل جائحة كورونا - طاهير, نادية (جامعة الوادي University of Eloued, 2021)
تهدف هذه الدراسة إلى إبراز دور جائحة كورونا في تطوير معاملات الدفع الإلكتروني في الجزائر، حيث سرّع فيروس كوفيد19 خطط الرقمنة، بفعل الحجر المنزلي وتقييد التنقل وفرض عقوبات على المخالفين لهذه الإجراءات، مما دفع العديد من المواطنين إلى اعتماد الدفع الإلكتروني في تسديد فواتيرهم واقتناء حاجاتهم، في وقت تحاول فيه السلطات استغلال هذا الزخم لتحفيز الاقتصاد عبر منافذ مستدامة. وتوصلت الدراسة إلى جملة من النتائج أهمها، أنّ الدفع الإلكتروني سجل قفزة نوعية في ظل جائحة كورونا، وذلك مع رغبة أعداد متزايدة من المواطنين تجنب استخدام النقود التقليدية، التي يسود الاعتقاد بأنها قد تكون موبوءة ، والتوجه نحو المعاملات غير النقدية، للتقليل من فرص انتشار الفيروس والإصابة بالعدوى. This study aims to show the role of the corona pandemic in the development of electronic payment transactions in Algeria, where the virus has accelerated digitization plans, due to home quarantine and movement restrictions, which prompted many citizens to adopt electronic payment for bills and daily needs, at a time when the authorities are trying to exploit this crowd to stimulate the economy through sustainable outlets. The study reached many results, the crucial one is that electronic payment recorded a quantum leap during the corona pandemic, with the desire of an increasing number of citizens to avoid using traditional money which may be infected and to move to non cash transactions, to reduce the spread of the virus and infection.
Electronic payment during the coronavirus pandemic - Algeria as a reference -
مقال
Keywords: الدفع الإلكتروني، وسائل الدفع الإلكتروني، جائحة كورونا، كوفيد19، الجزائر.